2016
DOI: 10.1111/aos.13156
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of retinal vascular calibres as a biomarker of disease activity in birdshot chorioretinopathy

Abstract: Purpose Birdshot chorioretinopathy (BCR) is a potentially blinding ocular disorder involving the retinal vasculature and choroid without any systemic manifestations. The objective of the study was to describe vascular calibre changes in BCR and analyse the possibility of this optical biomarker for staging and monitoring disease activity in BCR. Methods This retrospective case–control study at a tertiary referral eye centre in the UK included 33 eyes from 21 patients with BCR and equal number of eyes from contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Recently, Agrawal et al measured retinal vascular calibers in BCR patients and reported significantly impaired calibers only in the retinal venules compared to a healthy control group. 17 This finding suggests that microvascular inflammatory damage in BCR is primarily present in the venous arm.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Agrawal et al measured retinal vascular calibers in BCR patients and reported significantly impaired calibers only in the retinal venules compared to a healthy control group. 17 This finding suggests that microvascular inflammatory damage in BCR is primarily present in the venous arm.…”
Section: Discussionmentioning
confidence: 97%
“…Although our study failed to show any significant difference in CRAE, CRVE and AVR according to BSCR, Agrawal et al reported narrowing of retinal veins using the IVAN software (for n = 21 patients). (Agrawal et al, 2017) In this latter study, CRVE values were significantly lower for BSCR patients (211.3 μm) than in controls (227.9 μm). There was no evidence of significant for the CRAE between the two groups.…”
Section: Discussionmentioning
confidence: 56%
“…intrinsic vascular characteristics. Vascular patterns vary with extraocular factors, such as blood pressure, 32 and hematocrit, 33 and with local factors, such as retinal vein occlusion, 34 uveitis, 35 and diabetic retinopathy. 36 Consequently, the heritability of the retinal vascular fractal dimension could be mediated by other factors than the heritability of vascular characteristics, especially such systemic factors as the heritability of blood pressure control mechanisms.…”
Section: Discussionmentioning
confidence: 99%